Efficacy of abatacept and tocilizumab in patients with rheumatoid arthritis treated in clinical practice: results from the nationwide Danish DANBIO registry. Issue 7 (8th May 2011) - Leffers, Henrik Christian; Østergaard, Mikkel; Glintborg, Bente; Krogh, Niels Steen; Foged, Heidi; Tarp, Ulrik; Lorenzen, Tove; Hansen, Annette; Hansen, Michael Sejer; Jacobsen, Martin Skov; Dreyer, Lene; Hetland, Merete Lund
Abstract : Objectives: To describe drug survival, disease activity and clinical response in patients with rheumatoid arthritis (RA) treated with abatacept or tocilizumab in routine care, based on prospectively registered observational data from the nationwide Danish DANBIO registry. Methods: 150 Patients with RA treated with abatacept and 178 treated with tocilizumab were identified. Drug survival was investigated. Response data were available in 104 and 97 patients, respectively. Changes in 28-joint Disease Activity Score (DAS28) based on C-reactive protein (CRP) and European League Against Rheumatism (EULAR) response after 24 and 48 weeks were investigated. No direct comparison of drugs was made. Results: Median (IQR) disease duration was 8.5 (3–14)/9 (3–12) years (abatacept/tocilizumab). 95%/93% of patients had previously received one or more tumour necrosis factor inhibitor (TNFi). After 48 weeks, 54%/64% of patients (abatacept/tocilizumab) maintained treatment. Among patients with available response data, DAS28 was 5.3 (4.7–6.1), 3.4 (2.7–4.9) and 3.3 (2.5–4.3) at baseline, weeks 24 and 48, respectively, in the abatacept group and 5.4 (4.7–6.2), 2.9 (2.3–4.0) and 2.5 (1.9–4.5) in the tocilizumab group. At weeks 24 and 48, the remission rates for abatacept/tocilizumab were 19%/39% and 26%/58%, respectively. EULAR good-or-moderate response rates were 70%/88% and 77%/84%, respectively. The decline in DAS28 variables over time appeared similar between drugs, except for CRP, which seemed to decline more rapidly among tocilizumab-treated patients. Conclusions: In patients with RA (≥90% TNFi failures), a good-or-moderate EULAR response was achieved in ≥70% of patients treated with abatacept or tocilizumab for 24 weeks in routine care. Apparent declines in DAS28 variables over time were similar between drugs, except for the more rapid CRP decline among tocilizumab-treated patients, directly caused by interleukin 6 inhibition.